2011
DOI: 10.1016/j.visres.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cerebellar disease on sequences of rapid eye movements

Abstract: Summary Studying saccades can illuminate the more complex decision-making processes required for everyday movements. The double-step task, in which a target jumps to two successive locations before the subject has time to react, has proven a powerful research tool to investigate the brain’s ability to program sequential responses. We asked how patients with a range of cerebellar disorders responded to the double-step task, specifically, whether the initial saccadic response made to a target is affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Inactivation did not alter saccade velocity, acceleration, and duration, or the coefficient of variation of latencies in any condition, except for contraversive anti-saccade deceleration (paired t test, p ϭ 0.04; Table 1). These results suggest that inactivation of the dentate nucleus in our experiments did not alter neuronal activity in the oculomotor-related regions in the interposed and the fastigial nuclei that directly control saccade dynamics (Robinson and Fuchs, 2001;Iwamoto and Kaku, 2010).…”
Section: Effects Of Local Inactivationmentioning
confidence: 65%
See 3 more Smart Citations
“…Inactivation did not alter saccade velocity, acceleration, and duration, or the coefficient of variation of latencies in any condition, except for contraversive anti-saccade deceleration (paired t test, p ϭ 0.04; Table 1). These results suggest that inactivation of the dentate nucleus in our experiments did not alter neuronal activity in the oculomotor-related regions in the interposed and the fastigial nuclei that directly control saccade dynamics (Robinson and Fuchs, 2001;Iwamoto and Kaku, 2010).…”
Section: Effects Of Local Inactivationmentioning
confidence: 65%
“…Cerebellar Crus I and II constitute a large portion of the primate cerebellar hemispheres, and send outputs to the ventral part of the dentate nucleus, which in turn transmits signals to the frontal and parietal cortices via the thalamus (for review, see Ramnani, 2006;Strick et al, 2009;Prevosto et al, 2010;Lu et al, 2012). This portion of the cerebellum appears to be involved in higher-order cognitive functions, such as executive function and motor planning, rather than the on-line adjustment of movement parameters (Leiner et al, 1986;Ito, 2002;Bellebaum et al, 2012;Stoodley et al, 2012). In this study, we found many saccade-related neurons in the ventral posterior portion of the dentate nucleus that might transmit signals from the lateral cerebellum to the medial and lateral prefrontal cortex.…”
Section: Roles Of the Lateral Cerebellum In Anti-saccadesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prior study, 1 we showed that in response to the rapid presentation of a sequence of two visual stimuli (double‐step paradigm), cerebellar patients showed greater inaccuracy of their first saccade compared with saccades made to single target jumps. Moreover, cerebellar patients often failed to make a saccade to the first target jump.…”
Section: Introductionmentioning
confidence: 86%